Faktor-Faktor Motivasi Kerja Tenaga Kerja Proyek Konstruksi di Kota Palangka Raya - Nurtika; Rudi Waluyo; Waluyo Nuswantoro (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
A construction project is a series of activities carried out with limited time and resources to achieve certaingoals. Resources are one of the factors that determine the success of a construction project, without a numberof resources that assist in the implementation process, construction projects will not be completed. Humanresources are one of the factors that determine the success of a construction project, where human resourceshave an important influence in terms of material factors, machines, money, and methods. One of the resourcesdirectly involved in carrying out construction work is a skilled workforce in the field (craft labor) consistingof builders with various types of specific expertise. In addition to the human resource aspect, the motivationalaspect is also very important. Motivation is everything that encourages or motivates someone to do somethingwith a specific purpose. The concept of motivation applied in the work environment is expected to provide animpetus to increase the enthusiasm of the workforce in the construction industry, in order to achieve the successof a project in terms of discipline and time. This article aims to determine the work motivation factors ofconstruction workers in Palangka Raya City. The method used is a literature study on the motivational factorsof workers in construction projects, by comparing several related journals. The results show that there are 28sub-factors of work motivation in construction workers based on the 5 factors of Abraham Maslow's theory ofneeds.